AKSES TANAH DAN KENDALA LEGITIMASI EKS PENGUNGSI TIMOR TIMUR DI KABUPATEN BELU - Farid Abud Alkatiri (Jurnal Kawistara, 2018)
Land exclusion has been an issue for the majority of the former East Timorese in Belu regency. The resettlement was offered as one of the the government’s programs. Unfortunately, the program has not provided sufficient land to be accessed due to legitimation of the social institution. As a consequence of land exclusion, there have been various land conflicts between the refugees and the landlords. This aim of this research is to investigate the land exclusion issue caused by the power of legitimation. Some previous studies have been conducted to understand the problem, using conflict and public policy approaches to see why the issue has been occurring since 1999. Meanwhile, this article analyzes the legitimation of social institution and the roles of certain local figures in shaping land exclusion. To analyze the issue, this research uses social exclusion theory, specifically powers of exclusion, where legitimation as one of the essential issues. This research uses qualitative method, and the data is collected through in-depth interviews and secondary sources. The result of the research shows that majority refugees have faced difficulties to access to the land due to the legitimation of traditional institution (lembaga adat) and the role of local community leaders.